2012
DOI: 10.1007/s11548-012-0743-0
|View full text |Cite
|
Sign up to set email alerts
|

A fluorolaser navigation system to guide linear surgical tool insertion

Abstract: Quantitative and qualitative evaluations of the fluorolaser navigation system show that it can support accurate guidance and intuitive surgical tool insertion procedures without preoperative 3D image volumes and registration processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Thus, improved accuracy may follow recalibration. Screw plans are evaluated in differing ways in the literature; Liang et al [12] compute position and orientation errors by comparing screw placements to a ground truth plan, Kawaguchi et al [9] determine critical breaches of the screws using postoperative CT, and Zhang et al [22] use perforation of the pedicle wall and deviation from the lateral pedicle wall. Following these evaluation methods, we reported both the position and orientation accuracy of the TUSS-registered screw plans-with reference to the ground truth plans-and also examined the registered plans for pedicle wall perforations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, improved accuracy may follow recalibration. Screw plans are evaluated in differing ways in the literature; Liang et al [12] compute position and orientation errors by comparing screw placements to a ground truth plan, Kawaguchi et al [9] determine critical breaches of the screws using postoperative CT, and Zhang et al [22] use perforation of the pedicle wall and deviation from the lateral pedicle wall. Following these evaluation methods, we reported both the position and orientation accuracy of the TUSS-registered screw plans-with reference to the ground truth plans-and also examined the registered plans for pedicle wall perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Although this robot provides excellent clinical outcomes [7], its cost and complexity, which are far greater than our TUSS-based system, may impose limitations on its applicability as the standard of care. In other approaches, Liang et al [12] used the intersection of two laser planes to guide the pedicle probe to position the guidewires for screws and Von Jako et al [20] used electromagnetic tracking in minimally invasive percutaneous pedicle screw placement. Although these two technologies reduce the use of fluoroscopy during the procedure, they do not eliminate radiation entirely like our TUSS-based system does.…”
Section: Discussionmentioning
confidence: 99%
“…The positions of the camera and the patient are determined by measuring distances between individual trackers and markers. Several studies reported using a set of infrared markers [ 4 , 10 , 13 , 33 , 37 40 ]. A newer approach suggested by Wild et al [ 41 ] involved using fluorescent markers during laparoscopic procedures.…”
Section: Resultsmentioning
confidence: 99%
“…An exact comparison of accuracy between specific studies is impossible due to variable conditions and different approaches for measuring accuracy. Optical systems feature precision within 5 mm in several studies [ 8 , 10 , 15 , 18 , 35 , 37 , 44 , 57 59 ], which is considered sufficient for clinical application. The required precision differs greatly among various procedures and should be determined individually.…”
Section: Resultsmentioning
confidence: 99%
“…However, the predetermined template image might become invalid and thus may cause identification failure. During the calculation of mutual information, threshold value selection presents a problem, which cannot be determined unless a numerous experiments and tests are performed [11][12][13][14][15][16]. Li et al [10] proposed the use of clustering algorithm for the automatic identification of information on the mark points and determination of the grid posture of the marked points through the table of row/column index.…”
Section: State Of the Artmentioning
confidence: 99%